2021
DOI: 10.1016/j.ijid.2021.07.076
|View full text |Cite|
|
Sign up to set email alerts
|

Kyasanur Forest Disease, is our surveillance system healthy to prevent a larger outbreak? A mixed-method study, Shivamogga, Karnataka, India: 2019

Abstract: Background: Kyasanur Forest disease (KFD) is a tick-borne zoonosis that is endemic in Karnataka. Against the backdrop of the recent geographical expansion of KFD, indicating the inadequacy of policy and surveillance systems, the present study was performed to evaluate the KFD surveillance system in Shivamogga. Methods: US Centers for Disease Control and Prevention guidelines for surveillance system evaluation were followed. Nine attributes of the system towards its objectives were evaluated in a mixed study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Furthermore, weekly updates on the status of outbreaks, such as disease progression and applied interventions, were sometimes missing. Our finding is consistent with another study in Karnataka that found similar reporting delays and data quality issues; That study concluded that the KFD surveillance conducted at the district and state level might not have fully integrated with the national IDSP portal system 56 . Moreover, KFD case reporting systems were not maintained by health authorities at the state or district level.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, weekly updates on the status of outbreaks, such as disease progression and applied interventions, were sometimes missing. Our finding is consistent with another study in Karnataka that found similar reporting delays and data quality issues; That study concluded that the KFD surveillance conducted at the district and state level might not have fully integrated with the national IDSP portal system 56 . Moreover, KFD case reporting systems were not maintained by health authorities at the state or district level.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is still a need to strengthen surveillance activities, implement unified data reporting protocols and tools in all states, and adopt transparent data sharing practices. This issue has also been raised by Bhat et al [30] who found that human case reporting measures are not standardized across local public health centers; there were delays in testing, lack of systematic data sharing practices, outdated surveillance guidelines, limited vaccine production capacity, inconsistent training and attitudes among surveyed personnel, and inadequate operational research.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that public health agencies standardize their reporting format for KFD for human cases, deaths, and monkey deaths systematically, which is maintained in the same format for all the KFD states [7 , [30] , [31] , [32] . Investing in open and transparent data reporting practices and effectively training staff and personnel in disease reduction and prevention measures is crucial.…”
Section: Discussionmentioning
confidence: 99%